2011
DOI: 10.1111/j.1365-2125.2011.03915.x
|View full text |Cite
|
Sign up to set email alerts
|

Prescribing of medicines in the Danish paediatric population outwith the licensed age group: characteristics of adverse drug reactions

Abstract: WHAT IS ALREADY KNOWN ABOUT THIS SUBJECT• Off‐label use of medicine in children is common, as few medications are licensed for use in this population.• There is concern about off‐label use of medicines in children due to lack of knowledge about safety beyond the indication area described in the official product information documented in the licensing material.WHAT THIS STUDY ADDS• One‐fifth of all ADRs reported over a decade in Danish children were associated with off‐label prescribing of medicines.• Serious A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
30
0
2

Year Published

2011
2011
2018
2018

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(33 citation statements)
references
References 26 publications
1
30
0
2
Order By: Relevance
“…The fifth factor is associated with preoccupations and concerns about side effects of medications in the future. Concerns about future side effects of medications, a recurrent topic in these families, is somehow coherent with recent publications in scientific journals [1,16] and with what parents may read in the media or hear on the news [23]. Once again, it is crucial that clinicians prescribe treatments according to current guidelines [30,50], and that side effects of the medications are monitored and prevented [27].…”
Section: Discussionmentioning
confidence: 89%
“…The fifth factor is associated with preoccupations and concerns about side effects of medications in the future. Concerns about future side effects of medications, a recurrent topic in these families, is somehow coherent with recent publications in scientific journals [1,16] and with what parents may read in the media or hear on the news [23]. Once again, it is crucial that clinicians prescribe treatments according to current guidelines [30,50], and that side effects of the medications are monitored and prevented [27].…”
Section: Discussionmentioning
confidence: 89%
“…8 In 25 As concluded in the review from Mason et al, 28 it seems that there is no consistent evidence suggesting a greater risk related to off-label prescribing, perhaps because of the heterogeneity in prescribing settings or practices considered in the studies. Indeed, some studies found high rates of off-label prescribing of mental health or cancer medications.…”
Section: Studies Investigating Adr Occurrence In Outpatient Settingsmentioning
confidence: 96%
“…A high incidence of unapproved use of drugs (prescribing outside the recommended dosage, indication, route of administration, or age of patient) and unlicensed use of drugs in the pediatric population has been reported [28]. A study conducted in the Europe and Australia indicated that 80 -93 % of neonatal medications were off-labelled or unlicenced, with an overall off-label prescription rates of between 25 % and 60 % across populations and mostly seen in children less than 2 years of age and also in adolescents [29,30].…”
Section: Discussionmentioning
confidence: 99%